Knowledge metamodel for crowdsourcing innovation intermediaries - Silva, Cândida (2022)
Open innovation is a hot topic in innovation management characterized by a new form of interacting and collaborating with the external environment of a company to innovate more successfully and with less costs. Chesbrough (2006) advocates that firms can and should use external ideas as well as those from their own R&D departments, and both internal and external paths to the market in order to advance their technology. Crowdsourcing innovation presents as a derivation of this new paradigm taking advantage of the Web 2.0 tools to generate new ideas through the heterogeneous knowledge available in the global network of individuals with easy access to information and technology. So, crowdsourcing innovation brokers facilitate the access to a vast open and global knowledge community, and provide support in integrating contributions, as well as managing and motivating the crowd participants. This paper presents a literature review of open innovation models and innovation intermediaries functions' and proposes a knowledge's metamodel for crowdsourcing innovation intermediaries.